Conflitos de agência e alinhamento de interesses: enforcement e incentivos sob uma análise econômica - Cardoso, Matheus Filipe Poletto (2022)
The delegation of powers between principals (shareholders, owners) and agents (directors, administrators), separating control from the ownership of a company, is fertile ground for opportunistic behavior and conflicts of interest. Considering that the structural basis of these relationships is composed, as a rule, by legal, corporate governance and contractual norms, the impact of such regulations was analyzed, as well as the existence of flaws that would allow the facilitation of opportunism in business relationships. We have found that the fiduciary relationship must be guided by the sum of positive and negative incentives, rules and standards, reputational risks, and rewards, etc. In addition, it was found that several incentive strategies have great chances of distortion, increasing the benefit of opportunistic behavior, as well as that governance norms and Laws, without due enforcement, do not have a broad effectiveness, in isolation, to mitigate these problems. This work demonstrates the importance of using interdisciplinarity between Law and Economics, as well as strategic thinking when drawing up rules of behavior, the importance of incentives and enforcement, and the need for joint use of control and inspection mechanisms and contractual instruments. We seek to demonstrate that, and how, internal institutions, if formulated in an economically skillful way, are able to impose positive incentives, aligning the interest between the parties, and negative ones, increasing the cost of dishonesty among those who have fiduciary duties in the business environment.